The impact of managers’ leadership styles on developing social capital directed towards mainstreaming organizational citizenship behavior in their organizations : an analysis of the views of managers in a number of university colleges and institutes and c - Abdul Sattar Mohammed Ali; Maysoon Abdullah Al-Shalama; Athmar Abdul Razzaq Muhammad (Iraqi Journal for Administrative Sciences, 2025)
This research aims to determine the contribution of leadership styles of managers of different kinds of autocratic, democratic and permissive in the development of the capital of their organizations, social-oriented organizational citizenship behavior of circulating them. After he finished the researchers preparing systematic searching, including the form-resolution five-year measure, which they prepared in accordance with the contexts of science in the preparation of fold, and requires the theoretical framework appropriate for the definition of variables, their research (leadership styles and social capital and the behavior of citizenship, organizational), they began analyzing data that were collected of asample of their research of a number of heads of academic departments in the faculties of the University of Mosul, institutes and faculties of the technical education in this city\\\\'s (76) Head of Department, has reached a set of results, which were in their light out a number of conclusions, perhaps the most important of which are confirmed, the point of their view that they announce it this summary, as well as evidence of different types of leadership styles in the levels of impact in both social capital and citizenship behavior under examination. In the light of, inter their findings, researchers presented their proposals, have demonstrated the most important of the need to seek managers towards the development of the capital of social organizations because of its effect proved Manueth in this research down to the universal behavior of citizenship regulators in these organizations to achieve their objectives on the one hand and the service of their country, on the other. The impact of spiritual work in the performance of employees and reflected in the assessment and organizational units Case study in the Mosul Technical Institute.